Islamist Extremism, Propaganda, And New Media: A Case Study of @Mutiaradabiq During the COVID-19 Pandemic - Suheri, Suheri (Universitas Islam Negeri Sunan Kalijaga, 2023)
The activities of Islamist extremist actors are increasingly intensive during the COVID-19 pandemic, in which they are progressively active in producing Islamist narratives in cyberspace. Strategic communication is one of the techniques for Islamist extremist groups to perpetuate their influences on society through social media during the COVID-19 pandemic. Thus this research aims to study propaganda as part of strategic communication in Islamist extremist activities during the COVID-19 pandemic (2020-2021), primarily through Facebook @MutiaraDabiq. This research considers that strategic communication and propaganda are two interrelated communication entities. This study is qualitative research and uses critical discourse analysis (CDA) as a method of data analysis. This research argues that propaganda on social media worked significantly through verbal and visual discourse uploaded by Islamist extremist actor, who reveals rational connections between language use and social reality. This study found how the existences propaganda of this Facebook account can exist during the COVID-19 pandemic by; first, strategic communication emerges into instrumental propaganda at the @MutiaraDabiq performance, and second, strategic communication flourish in discourse logic at the @MutiaraDabiq account.